Management Factors Affecting the Academic Management Competencies of Administrators Under the Chaiyaphum Primary Educational Service Area Office 2 - Klinsupan, Supawadee; Poopayang, Piangkhae (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of this research were: 1) to study the management factors of the administrators under the Chaiyaphum Primary Educational Service Area Office 2; 2) to study the academic management competencies of the administrators under the Chaiyaphum Primary Educational Service Area Office 2; 3) to study the relationship between management factors that affecting the academic management competencies of the administrators under the Chaiyaphum Primary Educational Service Area Office 2; 4) to build the prediction of factors that affecting the academic management competencies of the administrators under the Chaiyaphum Primary Educational Service Area Office 2. Results 1) The management factors of the administrators under the Chaiyaphum Primary Educational Service Area Office 2, overall, at a high level. 2) The academic management competencies of the administrators under the Chaiyaphum Primary Educational Service Area Office 2, overall, at a high level. 3) There was a positive correlation between administrative factors and academic administration performance in schools under Chaiyaphum Primary Educational Service Area Office 2 at a relatively low to moderate level. statistically significant at the .01 level. 4) Administrative Factors Affecting Academic Management Performance of School Administrators Under the Office of Chaiyaphum Primary Education Service Area 2, there were 2 factors: self-confidence factor (X3), responsibility factor (X6), multiple correlation was .584, and predictive coefficient or predictive power was 34.10%. statistically significant at the .01 level with a value The coefficients of predictive variables in raw score form (b) were .127, 282, respectively. The predictor coefficients in standard score () were .220, .406, respectively, and the predictive equation constant in The raw score figure (a) is 1.863.